The relationship between screen time and overweight/obesity among adolescents in Addis Ababa, Ethiopia - Asnake, Wubetsh; Endris, Bilal Shikur; Gizaw, Muluken (Research Journal in Medical and Health Sciences, 2023)
The study aimed to ascertain how screen time and adolescent overweight/obesity relate to one another. A school-based cross-sectional study was conducted among adolescents in Addis Ababa, Ethiopia. The sample size was calculated using the single population proportion formula, and the final sample size was 550. Data was collected using interviewer-administered questionnaires. SPSS software version 20 was used to perform descriptive statistics, bivariate analysis, and multivariate logistic regression analyses. The study found that the mean screen time in the study population was 4.12.2 hrs. per day, and the prevalence of overweight and obesity was 12.3% and 1.85%, respectively. Female sex, high socio-economic status, high screen time, eating habits while watching TV, and physical activity were found to have a significant association with overweight/obesity. This study demonstrated a 53.7% prevalence of screen time above the recommended amount and a positive association between longer periods of screen time and overweight/obesity among adolescents in Addis Ababa. Parents and adolescents should be aware of this association and encouraged to involve their children in other forms of recreational activity.